Penerokaan pengetahuan teknologi, pedagogi dan kandungan dalam kalangan guru prasekolah di daerah Sandakan, Sabah / Jain Chee - Jain, Chee (2017)
This study aims to explore the Technological Pedagogical Content Knowledge (TPACK) of preschool teachers. The main aspect being explored is the Content Knowledge (CK), Pedagogical Knowledge (PC) and Technological Knowledge (TK) through inquiring the participants‟ understanding of the preschool curriculum content (called Kurikulum Standard Prasekolah Kebangsaan or KSPK), and how participants transform the knowledge into lesson plans and classroom teaching practice in preschool. This is a qualitative case study design with four preschool teachers chosen as participants. The data collected through interviews protocol, teaching observation protocol and document analyzing for six months. The main interview and critical incidents interview was done to inquire the background of the participants and their knowledge of the KSPK, while pre-and post-teaching interviews were held to obtain more information regarding a lesson through teaching observation. The teaching observation of lesson was done by video recordings and field notes to explored participant‟s knowledge of teaching preparation and teaching skills in preschool classroom and analysis of the content of the document based on the purpose of the study. Data was analyzed based on Miles and Huberman (1994). Meanwhile, validity and reliability based on triangulation method, pilot study, reseach participants‟ validation, Cohen Kappa Index Scale and the duration of the study. The findings of this study show that participants‟ knowledge of concepts, subject contents and learning outcomes are not in accordance with KSPK and teaching with technology, however, the participants‟ very good knowledge and understanding in pedagogy. The study also found that knowledge and understanding TPACK still not fully, emphasizes on teaching planning and preparation of lesson plans while the implementation of teaching is more focused on skills in reading, writing and mathematics to prepare pupils to Year One, compared to teaching activities to produce balance humanism in terms of physically, mentally, emotionally, spiritual and personality. This study also suggests a conceptual framework of professional knowledge of teachers – teaching duties, based on findings.